2019
DOI: 10.1097/md.0000000000017258
|View full text |Cite
|
Sign up to set email alerts
|

β-3 adrenergic receptor gene polymorphisms are associated with gestational diabetes mellitus in a Chinese population

Abstract: Increasing studies demonstrated that genetic susceptibility attributes to the development of gestational diabetes mellitus (GDM). The polymorphisms of the β-3 adrenergic receptor(β-3AR) gene have been found to be of great importance in bodyweight elevation and dyslipidaemias. We aimed to determine the influence of β-3AR polymorphisms on the GDM risk. Thus, we performed a case-control study including 136 GDM cases and 138 controls to evaluate the relation between the rs201607471 and susceptibility to GDM. Likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The ADRB3 gene is located on human chromosome 8p11.23, encoding ADRB3, which is primarily expressed in the adipose tissue. It is a member of the G protein-coupled receptor superfamily that mediates heat generation and fat decomposition stimulated by catecholamines and occupies a significant position in the activation of energy storage and utilization of lipid decomposition and internal environmental stability of glucose [69][70][71][72]. Therefore, the gene expression defect caused by an ADRB3 mutation is the initial factor in insulin resistance [70].…”
Section: Genes Involved In Glucose Metabolism and Insulin Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…The ADRB3 gene is located on human chromosome 8p11.23, encoding ADRB3, which is primarily expressed in the adipose tissue. It is a member of the G protein-coupled receptor superfamily that mediates heat generation and fat decomposition stimulated by catecholamines and occupies a significant position in the activation of energy storage and utilization of lipid decomposition and internal environmental stability of glucose [69][70][71][72]. Therefore, the gene expression defect caused by an ADRB3 mutation is the initial factor in insulin resistance [70].…”
Section: Genes Involved In Glucose Metabolism and Insulin Resistancementioning
confidence: 99%
“…It is a member of the G protein-coupled receptor superfamily that mediates heat generation and fat decomposition stimulated by catecholamines and occupies a significant position in the activation of energy storage and utilization of lipid decomposition and internal environmental stability of glucose [69][70][71][72]. Therefore, the gene expression defect caused by an ADRB3 mutation is the initial factor in insulin resistance [70]. Guan et al, in a meta-analysis of five studies that included 1239 participants with GDM from four Caucasian and one Asian region, demonstrated that the Trp64Arg (rs4994) polymorphism in ADRB3 was associated with GDM susceptibility in Caucasian populations in Europe [73].…”
Section: Genes Involved In Glucose Metabolism and Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Genetic factors, including IR and IRS1 gene polymorphisms [ 48 ], directly affect insulin signaling. In addition, polymorphisms of other genes, such as the beta 3 adrenergic receptor gene [ 49 ] and the uncoupling protein gene [ 50 ], lead to insulin resistance by favoring abdominal obesity. Several molecular mechanisms, including apoptosis, oxidative stress, mitochondrial dysfunction, and inflammation, are all involved in insulin resistance [ 44 , 51 ].…”
Section: Type 2 Diabetesmentioning
confidence: 99%